Arthroscopic Repair of the Bankart Lesion Using Dual-Row Labral Repair - Bryan Loh MBBS; Denny Tjiauw Tjoen Lie FRCS (SAGE Publishing, 2021)
Background: The most common technique described for bankart repair is the single-row labral repair. Recent interest has been the use of a dual-row, double pulley technique, first described by Zhang et al and popularized by Millett et al as the "bony Bankart bridge" technique. The aim of this study is to report a double-row all-suture labral fixation technique using knotless anchors. Technique: Step 1: glenohumeral debridement, and preparation of the glenoid labral and Bankart. The patient is first placed in the beach-chair position and surface landmarks are created. The standard posterior portal is first created and the glenohumeral joint is evaluated. Once the lesion is identified, the relevant working anterosuperior and anteroinferior portals are established using the outside-in technique. The synovitis is debrided to allow visualization and the labrum is liberated from the anterior glenoid. The Bankart lesion fragment is liberated, and partial fragments are osteotomized. With the anterolateral portal as the viewing portal, the anterior rim of the glenoid is now decorticated using a motorized shaver and rasp to create a bleeding bony surface. Step 2: the low rim anchor (5:30 o'clock). At the anterior-inferior aspect of the glenoid, the drill guide is positioned as low as possible (5:30 o'clock position for the right shoulder) and about 7 to 10 mm medial to the rim of the glenoid. The first 1.8 mm single-loaded suture anchor (Q-FIX All-Suture Anchor) is then inserted via the posterior portal. Step 3: the anterior-inferior-medial (AIM) anchor (4 o'clock). Step 4: the knotless high rim anchor (3 o'clock). Step 5: tying of sutures. The sutures from each anchor are tied in a mattress configuration, eventually creating a suture bridge over the labral repair Discussion/Conclusion: This dual row labral repair technique allows for maximum compression and contact between the fragment and the glenoid bed, allowing healing over a contact area rather than just the rim. The other added advantage is the use of curved tip anchors which allow negotiation of difficult corners, especially in the 5 to 6 o'clock position.